Causes of variation in growth rate of reindeer calves - Petersson, C. J.; Danell, B. (Rangifer, 1993)
Weights of individual reindeer calves were registered on 3 or 4 occasions from the July roundup to the last slaughter roundup in January during each of four consecutive years (1986 to 1989). The observations were made in a tagged herd located in the southern part of the reindeer area in Sweden (63°N, 12°E). A total of 10 400 live-weight measurements were made, and the relationship between pre-slaughter weight and carcass weight was estimated using data from 109 individuals. Variation in weight and weight gain between weighing occasions was related to sex, number of days in the corral, scale and year. Non-linear growth curves were fit to the adjusted weights. For each sex, smoothed average weights and dispersions, both within and between year, as well as the coefficient of variation were calculated from data generated from the estimated functions. Individual calf weights were shown to be influenced by sex, weighing day within occasion, and by year. Reindeer calves gained between 20 and 25 kg in live body weight from two to 6-8 months of age. Male calves were heavier than female calves over the whole period and they gained in live weight on average 10 g/day more than female calves. Between year coefficient of variation was between 1.5 and 7% with the largest variation between years for July and January weights and the lowest variation for September weights. The growth curves showed that the major increase in weight was between July and September. From September to December/January the additional increase was only 5%. Dressing-percentage was influenced by live weight prior to slaughter. A positive relationship between live weight and dressing percentage was shown.